Case Series of 5 Patients with End‐Stage Renal Disease with Reversible Dyspnea, Heart Failure, and Pulmonary Hypertension Related to Arteriovenous Dialysis Access. (1st June 2015) - Raza, Farhan; Alkhouli, Mohamad; Rogers, Frances; Vaidya, Anjali; Forfia, Paul
Abstract : Patients with end‐stage renal disease (ESRD) with arteriovenous dialysis access (AVDA) can develop symptoms of heart failure and pulmonary hypertension (PH). We report on 5 patients with ESRD and AVDA who presented with shortness of breath, heart failure, and PH. All patients had partial or complete closure of AVDA and were reevaluated after AVDA revision. All 5 subjects had clinical and echocardiographic evidence of heart failure, hypertensive heart disease, left ventricular diastolic dysfunction, and PH at baseline. After complete closure ( n = 4) or partial banding ( n = 1) of AVDA, mean New York Heart Association class improved from 3.4 ± 0.4 to 1.8 ± 0.4 ( P = 0.016). Mean 6‐minute walk distance improved from 236 ± 115 to 366 ± 51 m ( P = 0.021). Serial echocardiography revealed a decrease in the right ventricle: left ventricle ratio from 1.12 ± 0.17 to 0.8 ± 0.06 ( P = 0.005) and improved diastolic dysfunction parameters. On right heart catheterization before definitive AVDA revision, acute manual fistula or graft occlusion led to an average decrease in cardiac output of 1.1 L/min with no other changes in hemodynamics: 9.88 ± 2.2 to 8.71 ± 2.2 L/min ( P = 0.059). However, the average decrease in cardiac output after definitive revision of the AVDA (mean, 90 days) was 4.0 L/min with marked improvements in biventricular filling pressures and pulmonary artery pressure. In patients with ESRD and AVDA presenting with heart failure and PH, revision or closure of AVDA can markedly improve dyspnea as well as the clinical, echocardiographic, and hemodynamic manifestations of heart failure and PH.